CHEAT ENGINE SCRABLE GAME DENGAN ALGORITMA GADDAG - Widjaja, Antonius (Universitas Katolik Soegijapranata, 2017)
Scrabble is a word game that tests the players vocabulary. The difficulty of this game depends on the players vocabulary knowledge. The more vocabularies known by the players, the easier it is to play. This project aims to help players who only know a few vocabularies by building a cheat engine application which implements GADDAG Algorithm. All vocabularies stored in trie data structure as a dictionary. This dictionary will be processed using GADDAG Algorithm to find all vocabularies that can be formed. This application will help player to find the vocabulary with the highest value.